The Association of Tattooing/Body Piercing and Psychopathology in Adolescents: A Community Based Study from Istanbul - SABUNCUOĞLU, OSMAN TALAT; TOPÇUOĞLU, VOLKAN (SPRINGER, 2012)
We aimed to investigate the association of psychopathology with tattooing and body piercing among adolescents in Istanbul by means of self-report questionnaires. Tenth, eleventh and twelfth grade students from 2 high schools in Istanbul with a total number of 607 participated in the study. The Youth Self Report, Children's Depression Inventory and a detailed semi-structured inquiry assessing tattooing, body piercing and some psychiatric and psychosocial variables were administered to the students. The prevalence of tattooing and body piercing were 4.8 and 7 %, respectively. The adolescents with tattooing and body piercing were found to have a higher frequency of alcohol and drug use, smoking, going to bars/night clubs and lower school grades when compared to those without tattooing and body piercing. Externalizing problems, mainly delinquent and aggressive behaviours were more prominent in the adolescents with tattooing and body piercing. Tattooing and body piercing in adolescents may be indicative of mental health risks.
Keywords: Tattoo; Body piercing; Adolescence; HIGH-RISK BEHAVIOR; COLLEGE-STUDENTS; BODY PIERCINGS; TATTOOS; INDICATORS